Role Of Plasmapheresis In 3% Yellow Phosphorus Poisoning And Its Outcome - Haneendhar R, Haneendhar R; V K, Sreelakshmi; Dominic, Melvin; Moturi, Sai Vineeth; Nivi P, Arul; Rathnasami, Pragnesh; Kalakkat, Alen Hussain (Journal of Neonatal Surgery, 2025)
Background and Objectives: Yellow phosphorus, commonly found in rodenticides, is a highly toxic substance frequently used in developing countries like India. Poisoning due to ingestion is often accidental or intentional, with a lethal dose of approximately 1 mg/kg. There is no specific antidote, and treatment primarily involves supportive care. This study evaluates the role of plasmapheresis in managing acute liver injury caused by yellow phosphorus poisoning. Methods: A retrospective case analysis was conducted at VMKVMCH, Salem, Tamil Nadu, on patients admitted with yellow phosphorus poisoning between January 2021 and March 2022. Medical records of these patients were reviewed. Baseline vital parameters and laboratory investigations (liver biomarkers, renal parameters, serum electrolytes, coagulation profile, arterial blood gas analysis, and imaging studies). Daily monitoring of blood investigations and clinical status. Statistical analysis using SPSS version 23, with numerical data presented as mean, standard deviation, and categorical data as percentages. Results: Early plasmapheresis (within 24 hours of ingestion) was associated with better clinical outcomes. Plasmapheresis reduced bilirubin, SGOT, SGPT, and INR levels significantly (p<0.05), though liver function parameters showed temporary elevation post-procedure. It was effective in preventing rapid deterioration, improving initial recovery, and stabilizing coagulation parameters. The overall survival rate was 67% in patients receiving plasmapheresis compared to a previously reported 76.2% mortality rate with standard care. Conclusion: Yellow phosphorus poisoning predominantly affects young adults, with a female preponderance. Acute liver injury develops within 3–4 days post-ingestion, and early plasmapheresis significantly improves prognosis. Patients presenting within 24 hours of poisoning respond well to treatment, reducing the need for liver transplantation. Plasmapheresis plays a crucial role in managing toxin-mediated acute liver injury and should be considered as an early therapeutic intervention.